Does customer engagement matter? Investigating brand trust toward insurance purchase intention in the post-pandemic era in Indonesia - I Made Sindhu Yoga; Ida Nyoman Basmantara; Nyoman Sri Manik Parasari (Management Institute Faculty of Economics Universitas Andalas, 2022)
Despite the urgency, the insurance penetration rate in Indonesia has been relatively low compared to other countries, even amid the pandemic. The lack of insurance literacy, trust in financial institutions, and the existence of asymmetry information has made people in Indonesia not purchase insurance products. The pandemic has caused people to realize how important insurance is to help their financial stability. Therefore, this study aimed to investigate customer behaviour in the insurance market during the post-pandemic. This research was conducted in Indonesia because of its low insurance penetration rate. The population of this research was insured people, while the sample's criteria were those aged between 30 to 55 years old, were guaranteed after the pandemic began, located in Indonesia, and still have an active income. This study used a quantitative method and measured the value weight using the 5-scale Likert Scale. The outcomes show that brand trust is vital in affecting insurance purchase intention. This research finds that customer engagement plays a positive but insignificant role in moderating the relationship between brand trust and purchase intention. The implications and suggestions also describe in this paper